ANALISIS FINANSIAL USAHA AGROINDUSTRI LEMPUK DURIAN (Studi Kasus : Agroindustri Lempuk Durian Elvia di Desa Bantan Tengah Kecamatan Bantan Kabupaten Bengkalis) - Indro Gustiawan; Yusmini '; Syaiful Hadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to analyze the financial feasibility and analyze the level of sensitivity on lempuk durian agro-industry. The case study method was used in the research, object of the research was lempuk durian Elvia agroindustry in Bantan Tengah Village Bantan Sub-district Bengkalis Regency. Investment criteria used in analyzing the financial feasibility were: Net Present Value (NPV), Internal Rate of Return (IRR) and Net Benefit Cost Ratio (Net B/C). The results showed that lempuk durian agroindustry was feasible and developed by the NPV of Rp.82.891.702 (NPV greater than zero), Net B/C of 3,06 (Net B/C is greater than one) and IRR are in DF 56,99% (IRR greater than 12% DF) within a period of production for three months each year in the durian season. The results of the sensitivity analysis showed that if the business runs the risk of the decrease in production of 5.43%, then lempuk durian agroindusrty was not sensitive to the risks incurred and the business is still feasible to run. Risks resulting in this business is not viable, if there is a sensitivity of 61% decline in production.   Keywords: lempuk durian agroindustry, financial feasibility, sensitivity